Determinants of Indonesian Palm Oil Export Volume - Ivan William Saragi; I Nyoman Mahaendra Yasa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Indonesia is the first palm oil producing country and palm oil exporter in the world. In recent years, the volume of Indonesian palm oil exports has decreased. The determinants of the volume of Indonesian palm oil exports are the United States dollar exchange rate, the area of ​​Indonesian palm oil plantations, and the price of CPO. This research aims to analyze the influence of the United States dollar exchange rate, oil palm land area, and CPO prices in the short term and long term, simultaneously and partially on the volume of Indonesian palm oil exports. The type of data in this research is secondary data in the form of quantitative data obtained from the Indonesian Central Statistics Agency (BPS), Bank Indonesia and the World Bank. This research was conducted in Indonesia from 1994-2023, with a total of 30 observations. The data analysis technique used is the Error Correction Model (ECM). The results of the research show that the US dollar exchange rate and the area of ​​Indonesian palm oil plantations in the short and long term have a significant effect, while the CPO price has an insignificant effect on the volume of Indonesian palm oil exports. The United States dollar exchange rate, the area of ​​Indonesian palm oil plantations, and the price of CPO simultaneously influence the volume of Indonesian palm oil exports. The United States dollar exchange rate has a partially negative and significant effect on the volume of Indonesian palm oil exports. The area of ​​Indonesian oil palm land has a partially positive and significant effect on the volume of Indonesian palm oil exports. CPO prices have a negative and partially insignificant effect on the volume of Indonesian palm oil exports.